2023
DOI: 10.3389/fpsyt.2023.1301714
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between thyroid-stimulating hormone, BDNF levels, and hippocampal volume in antipsychotic-naïve first-episode psychosis patients

Alba Toll,
Laura Blanco-Hinojo,
Daniel Berge
et al.

Abstract: IntroductionThyroid hormones play an essential role in hippocampal development, a key structure in psychosis. However, the role of these hormones in first-episode psychosis (FEP) has received limited attention. It has been hypothesized that thyroid hormones could cause morphological modifications in the hippocampal structure through the upregulation of brain-derived neurotrophic factor (BDNF). In this study, we primarily aimed to determine the relationship between thyroid-stimulating hormone (TSH) levels, peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In individuals with depression, one study revealed a correlation between elevated TSH levels, decreased serum BDNF levels, and a lower rise in BDNF during antidepressant treatment ( 41 ). A more recent study examining 50 patients undergoing their first episode of psychosis showed that high TSH levels were associated with low peripheral BDNF and reduced hippocampal volume, suggesting a potential neuroprotective effect of THs on the hippocampus ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with depression, one study revealed a correlation between elevated TSH levels, decreased serum BDNF levels, and a lower rise in BDNF during antidepressant treatment ( 41 ). A more recent study examining 50 patients undergoing their first episode of psychosis showed that high TSH levels were associated with low peripheral BDNF and reduced hippocampal volume, suggesting a potential neuroprotective effect of THs on the hippocampus ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using magnetic resonance imaging (MRI) in patients with untreated acquired hypothyroidism, a reduction in hippocampal volume has been observed ( 141 ), as well as a reduction specifically in the granular and molecular layers of the hippocampus ( 142 ). It has been proposed that the volume reduction correlates with a decrease in peripheral BDNF levels ( 143 ). In addition, using positron emission tomography (PET), it has been shown that hippocampal glucose utilization is reduced in hypothyroid patients ( 144 ).…”
Section: Acquired Hypothyroidism and Depression: Key Points On Mechan...mentioning
confidence: 99%